Efficacy and safety of direct‐acting antiviral therapy for hepatitis C virus in elderly patients (≥65 years old): A systematic review and meta‐analysis. Issue 7 (6th April 2022) - Lee, Jieun; Ahn, Sang Bong; Yim, Sun Young; An, Jihyun; Jun, Dae Won; Ko, Min Jung; Park, Dong Ah; Yoo, Jeong‐Ju
Abstract: Direct‐acting agents (DAAs) have launched a new era of hepatitis C virus (HCV) treatment. As aged individuals comprise a large percentage of HCV‐infected patients, the effectiveness and safety of DAAs in the elderly have come under scrutiny. This meta‐analysis aimed to evaluate the efficacy and safety of DAAs in elderly patients. After a systematic search in PubMed (MEDLINE), Embase, OVID MEDLINE, the Cochrane Library and other databases, two investigators reviewed relevant abstracts and selected manuscripts for examination. The sustained virologic response (SVR) and adverse event (AE) rates were calculated with a random‐effects model. Ninety studies evaluating SVR rates of elderly patients (≥65 years old) receiving DAAs were selected. DAAs in elderly patients exhibited a notable SVR rate of 96% (95% confidence interval [CI]: 95%–97%), accompanied by comparable rates in subgroup analyses. The comparison of SVR rates in elderly and non‐elderly patients indicated no significant discrepancy (odds ratio [OR] 1.01, 95% CI: 1.00–1.01). The overall event rate of AEs was 45% (95% CI: 31%–60%), though AE rates varied by subgroups. Furthermore, AEs were comparatively more frequent (OR 1.15, 95% CI: 1.04–1.28) in the elderly than non‐elderly, especially in subgroups such as SAE (OR 1.89, 95% CI: 1.52–2.36) and dose reduction in ribavirin (OR 1.90, 95% CI: 1.53–2.36). However, in the ribavirin (RBV)‐free regimen, there was no significant difference in the incidence of AEs between the elderly and non‐elderly groups. DAAs have high efficacy in elderly patients. Considering the possibility of AE, the RBV‐free regimen should be given prior consideration for the treatment of elderly patients with HCV.